ANALISIS TEKNIK PENERJEMAHAN IDIOM DALAM ROMAN BERSURAT ,,DIE LEIDEN DES JUNGEN WERTHERS” KARYA JOHANN WOLFGANG VON GOETHE - Gresia Demak Ruth Tania Saragih; Tarida Alvina Simanjuntak; Lidya Purba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify 1) Idiom in Epistolary novel ,, Die Leiden des jungen Werthers” by Johann Wolfgang von Goethe 2) Idioms translation techniques that used from epstolary novel ,,Die Leiden des jungen Werthers” to the roman Indonesian translation “Penderitaan Pemuda Werther”. Theory that used in this research is Higi-Wydler’s Idiom translation technique theory. The data source in this research is Epistolary novel ,, Die Leiden des jungen Werthers” by Johann Wolfgang von Goethe and the Indonesian translation in “Penderitaan Pemuda Werther” translate by Moh. Godjali Harun. The data were analyzed using qualitative descriptive techniques. The results of this study are as follows: there were 61 idioms that found in Epistolary novel ,,Die Leiden des jungen Werthers”, which of 60 idioms translated using idiom translation technique Null-Äquivalenz; 1 idiom was tranlated using idiom translation technique Partielle-Äquivalenz; no idioms were found that translated using idiom translation technique Totalle-Äquivalenz.